Dangerous pipelines, dangerous people: colonial ecological violence and media framing of threat in the dakota access pipeline conflict. Issue 2 (2nd April 2020) - Bacon, J. M.
ABSTRACT: Drawing on theories of settler colonialism, colonial ecological violence, and media framing this article considers how media framing contributes to the production of colonial ecological violence. Focusing on the case of the Dakota Access Pipeline (DAPL) I examine how local media deploys frames of risk and security in order to minimize or invalidate Indigenous responses to ecological harms as well as to legitimate violence against those who resist pipeline development.